PENGARUH STRATEGI EVERYONE IS A TEACHER HERE TERHADAP HASIL BELAJAR MATEMATIKA SISWA - ., Sulaiman (JURNAL E-DUMATH, 2016)
This research is a comparison study which intended to know the average ofstudentsâ result in learning mathematics taught by using everyone is a teacherhere strategy and taught by using expository on circle subject. The populationof this research is the eight graders in the even semester of SMP Negeri 1Sukoharjo in the academic year 2014-2015. The sample of the research is thestudents of the third grade. Sampling technique this research used clusterrandom sampling technique. The data analysis used t-test the statistics. Basedon the data analyzis it shows that there is an average difference on the resultsof from those who are taught by using expository and average result ofstudentsâ who are learning by using Everyone Is A Teacher Her Strategy arebetter than those who are learning by using expository.Keywords : everyone is a teacher here strategy , expository strategy, circle subject